Landscape in the teaching of urban geography:looks and experiences in the urban center of the municipality of Ipiaú –Bahia - Silva, Patrícia Ferreira; Trindade, Gilmar Alves (Revista Ensino de Geografia (Recife), 2019)
Urban landscapes are products of social processes and relationships that reflect the culture and way of life of such a society. Through technique, nature is transformed into expressed cultural objects and materialized in space. Society, as an integral part of its production, creates functions and forms that constitute the spatial organization, with different meanings according tothe experiences of each person; these factors allow the construction of global knowledge from the place where one lives, and place them in connection with ever more complex socio-spatial relationships. The objective of this work is to define possibilitiesof analysis, reading and representation of the landscape of the urban center of Ipiaú-BA, with the identification of its main signs, perspectives and tendencies that establish tools for the study of the urbanlandscape in the teaching of Geography in basic education. Theoretically, the work is based on the assumptions of Cultural Geography, highlighting also foundations of Humanistic Geography. The methodology sought to capture the signs and cultural elements present in the urban landscape of the Ipiaú Center, through the description and interpretation through photographic records, field research, as well as bibliographical and documentary research. The main signs and cultural elements identified in the centralurban landscape of Ipiaú were: the Cine Éden, the Mother Church of S. Roque, the St. Paula Building, the trade and the Rui Barbosa Square. The square is present as a place where these cultural elements, which are material, act as signs that stimulate immaterial relations that constantly construct and modify space